Analysis of the Implementation of Honda Motor ECU Remap in Increasing Customer Engagement and Sales - Putri Apriyani br Rangkuti; Nurlaila Nurlaila; Marliyah Marliyah (Universitas Pendidikan Indonesia, 2025)
This research aims to find out how the Panjol Motorbike repair shop can increase customer engagement and sales in its workshop business through the use of Honda Motor ECU Remap. By using an effective customer engagement strategy, workshop businesses can increase customer loyalty, retain existing customers, and increase new sales opportunities. The research method used is a qualitative descriptive method with data collection in the form of interviews and literature studies to strengthen the results of the writing. The results of the study show that the successful implementation of ECU remap at Bengkel Panjol increases customer engagement, satisfaction, and loyalty. However, sales at the Panjol Motorbike repair shop did not increase 100% due to the implementation of this ECU remap but from standard or daily services. The implementation of the remap has not fully increased workshop sales due to the lack of consumer understanding in suburban areas such as Tanjung Morawa. Several strategies, such as providing education to customers, conducting promotions, providing special packages to regular customers, and providing test drives and warranties can be carried out to increase customer engagement and sales in the future at the Tanjung Morawa District Panjol Workshop.